“I see things with parted eyes”: Shakespeare e a cultura do feminino em A Midsummer Night’s Dream - Santurio, Roberta Flores (2025)
This dissertation investigates the representations of the feminine in A Midsummer Night’s Dream (1595–6), by William Shakespeare, in light of the philosophical, religious, and scientific discourses that shaped the understanding of nature at the turn from the sixteenth to the seventeenth century. By blurring the boundaries between myth and matter, the play assembles female characters who seek to transcend the concreteness of the body and the subordination enforced by patriarchal logic, revealing a desire for transcendence. Hermia, Helena, Titania, and Hippolyta articulate modes of female subjectivity that resist the prevailing masculine culture, which associates the woman’s body with procreation, represses her interiority, and devalues her intellect. Traditionally interpreted as a cyclical space of reconciliation between couples, the forest in Dream is here analysed from a different perspective. Drawing on early modern conceptions of nature—marked by tensions between natural philosophy, theology, and emerging scientific paradigms—this study proposes that the forest constitutes a multifaceted symbolic arena of dispute between feminine and masculine forces, staging power dynamics, emotional volatility, and tensions between desire and normativity. In this contradictory setting, the aspiration toward immateriality is expressed through sensory practices, mythical imagery, and poetic articulations that expose the fractures of a world in transition. By weaving together mythology and Renaissance cosmology, Shakespeare fashions a theatrical space which, though aligned with aristocratic endorsement, is permeated by female voices that aspire to an alternative mode of existence beyond the confines of reproductive function. This cultural and ecofeminist perspective uncovers a veiled form of agency, sustained by a cultivated intellectuality. By investigating these dramaturgical fissures, this dissertation suggests that Shakespeare was already rehearsing, in this early comedy, an aesthetic sensitivity attuned to the complexity of the feminine, prefiguring concerns he would explore more deeply in his later plays.